English: English - Theressa Ayu Christiyanti; Irpan Ali Rahman; Lilie Suratminto (e-LinguaTera, 2025)
Figurative language is a way of expressing oneself using figurative words. This research aims to identify the figurative languages that are found in the movie script then analyze deeper the meaning and the role of it. This research is using descriptive qualitative method to analyze. The data was from movie script of “Fantastic Beasts: The Secrets of Dumbledore”. The research was using semantic approach, specifically figurative language. To identify the type of figurative language and its role to the movie, the writer use theory by Laurence Perrine (1956). The results of the study are, meaning of these figurative language can be deduced from the context, with Leech's theory revealing its depth. The most dominating figurative language found are Simile, Metaphor, Overstatement, Understatement, Irony, and Paradox. The study also found the functions of metaphorical language in constructing the film's message, influenced by Perrine's theory. There are 31 sentence of figurative language found in the movie, metaphor was predominate in the script and simile are use less frequently. This research seeks to contribute to a deeper understanding of figurative language along with its meaning and role in the “Fantastic Beasts: The Secrets of Dumbledore” film.